Integrating Food Sovereignty into Urban Planning: A Social Justice Perspective - Ergin, Mehmet; Yerliyurt, Bora (POLISH MINERAL ENG SOC, 2025)
As a result of population growth, globalization, wars, natural disasters and the climate crisis that has become more evident, it is seen that the problems related to food have reached a point that cannot be ignored. Until now, food problems have mostly been studied in fields such as food engineering, agricultural engineering and medicine. Studies in the field of planning, on the other hand, have mostly been limited to rural areas, and this problem has been discussed much less through urban areas and urbanization paradigms. Considering the current urbanization rates and planning paradigms, discussing the food problem through urban areas and producing solutions in these areas by the planning discipline can develop systemic solutions. Accordingly, the aim of this study is to filter the food literature through the planning framework and explore alternative solution areas. In accordance with the purpose of the study, some concepts have been examined hierarchically within the framework of urbanization and planning, while others have been excluded. The conceptual flow has followed both a chronological order and a deductive method in which one concept points to another concept. Therefore, the study follows a descriptive research method and looks for practical clues. As an auxiliary source, bibliometric analysis has been a quantitative method frequently used in the methodology. The concept sets that emerged from the bibliometric analysis were guided by the role of planning to examine the qualitative and structural dimension of the food problem. The role of the planning discipline in the conceptual flow centered on food safety, food security and food sovereignty has been examined, and food sovereignty, with which the relationship is more strongly established, has been scrutinized. Food sovereignty has come to the fore with the social justice dimension of planning and has been seen as more potential in producing planning policies. In the concluding section, a comparative conceptual analysis of the three concepts is made through the approach, main objectives, fields of action, key institutions, food-related policies, actors and concerns. The relationship between food sovereignty, which is seen to have stronger ties to planning, and the instrumental and qualitative dimensions of planning is revealed. Even the marginalization criticisms against food sovereignty have been seen to have a certain scope in planning. It is inevitable that qualitative and empirical studies will accelerate against the current and potential food crises in the current economic system, which is prone to crises. Although there is a lack of food issues in the literature, which has so far been associated with the rural dimension of planning, it is expected that food sovereignty, as a new area of discussion in planning, will also be discussed in urban areas, which host a large part of the population, and point to solution areas.
Keywords: food; food security; food sovereignty; equity; planning; urban planning; CLIMATE-CHANGE; SECURITY; GOVERNANCE; CHALLENGE; IMPACTS; SYSTEMS; PEASANT; CRISIS; LAND; Mining & Mineral Processing